Pelatihan Penanganan Kegawatdaruratan Tersedak Pada Anak di Desa Ledug Purwokerto - Sabna Meisya Lestari Sabna; Rahmaya Nova Handayani; Arni Nur Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Choking is a very dangerous emergency that often occurs in children under three years of age. Choking occurs when solid food that should pass through the digestive tract blocks the airway. Choking victims can lose consciousness, causing death. Treatment for choking in children is divided into three types, namely back blow, Heimlick maneuver and chest thrust. The aim of this Community Service is to identify the mother's level of knowledge and skills in handling choking emergencies in children. The method used is the lecture and demonstration method. There were 32 participants who attended and took part in the activity. The activity was carried out at RT.01/RW.05 Ledug Village, Purwokerto on Thursday, June 6 2024. The media used were powerpoint, leaflets and videos. Community Service Results showed that 19 participants (59.4%) had sufficient knowledge before the education was provided and after the education was provided, 29 participants (90.6%) were in the good category. The skill level before being given education and demonstration was that all participants were unskilled, 32 participants (100.0%), whereas after being given education and demonstration, 21 participants (65.6%) had skilled skills and 11 participants (34.4%) had less skilled skills. From the results of community service it can be concluded that there is an increase in knowledge and skills.